MODELS OF REFLECTIVISATION OF CONTAMINATED VOLITION IN DIALOGIC INTERACTION (ON THE BASIS OF VERBAL STATEMENTS IN THE SPANISH LANGUAGE) - Shevkun, Eleonora (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with the problem of simulation of the model of reflectivisation of contaminated volition. The article offers a new approach towads the concept of "contaminated volition" under the criteria of differentiation of lacunae in the epistemic domain of the subject of contaminated volition and its affective states. There have been differentiated certain types of consciousness – the epistemic sphere, which acts as the authority of the modal estimation, which is the basis of the simulation of the reflection of contaminated volition. According to the analysis of the correlations between the nature of the contamination of the volition, the individual sphere of consciousness, causing the modal estimation, and the means of their speech expression, the study discusses the biases in the non-prototype modal estimation of the volition through a series of gradual transitions in the continuum of modal meanings: the possibility – objective probability – subjective probability (chance) – a negative possibility. ___________ References • Dejk van T. A «Voprosy pragmatiki teksta.» Novoe v zarubezhnoj lingvistike 8 (1978): 259-336. • Jevropejs’kyj slovnyk filosofii’, pid ker. B. Kassen, K. Sigova, T. 1 (Kyi’v, Duh i litera, 2009), 530. • T. 3 (Kyi’v, Duh i litera, 2013), 486. • T. 4 (Kyi’v, Duh i litera, 2016), 276. • Ohrimenko, V. I. «Smyslova struktura modal’nyh odynyc’.» Monografija (Kyi’v, Logos, 2011), 255. • Pavilenis, R. I. «Ponimanie rechi i filosofija jazyka.» Novoe v zarubezhnoj lingvistike 17 (1986): 382. • Plungjan, V. A. Vvedenie v grammaticheskuju semantiku (Moskva, RGGU, 2011), 425. • Selivanova, O. O. Suchasna lingvistyka: Terminologichna encyklopedija (Kyi’v, Dovkillja-K 2006).